2018
DOI: 10.3934/biophy.2018.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule FRET reveals proofreading complexes in the large fragment of <em>Bacillus stearothermophilus</em> DNA polymerase I

Abstract: There is increasing interest in the use of DNA polymerases (DNA pols) in next-generation sequencing strategies. These methodologies typically rely on members of the A and B family of DNA polymerases that are classified as high-fidelity DNA polymerases. These enzymes possess the ability to selectively incorporate the correct nucleotide opposite a templating base with an error frequency of only 1 in 106 insertion events. How they achieve this remarkable fidelity has been the subject of numerous investigations, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Researchers assessed the family B DNA polymerase from Thermococcus kodakaraensis KOD1 (formerly Pyrococcus kodakaraensis KOD1)'s 3'-5'exonuclease (proofreading) activity and PCR performance (Kuroita et al, 2005). Christian et al (2018) observed the assembly of proofreading complexes and the migration of DNA pols of Geobacillus stearothermophilus along a DNA substrate by using smFRET.…”
mentioning
confidence: 99%
“…Researchers assessed the family B DNA polymerase from Thermococcus kodakaraensis KOD1 (formerly Pyrococcus kodakaraensis KOD1)'s 3'-5'exonuclease (proofreading) activity and PCR performance (Kuroita et al, 2005). Christian et al (2018) observed the assembly of proofreading complexes and the migration of DNA pols of Geobacillus stearothermophilus along a DNA substrate by using smFRET.…”
mentioning
confidence: 99%